Application GIS for detecting changes of Sungai Langat channel - Toriman, Mohd. Ikhwan (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2006)
Recent environmental developments have stimulated interests in the restoration and conservation of the Sungai Langat in Selangor both to protect against flooding and to maintain river bank stability. In order to support restoration and rehabilitation works of Sungai Langat, sufficient information on physical river characteristics are needed. The use of Geographical Information System (GIS) to map active channels and to categorised the reach according to sinuosity indices over time is encouraging. Total channel length in year 1996 reduced by about 16% from 1973. Avulsion and cut-off were observed at least at six stretches along the river. The sinuosity index (SINDX) varies from 0.61 to 2.31 in 1973 and 0.04 to 2.31 in 1996. At downstream, the channel tends to be more stable and straighter with SINDX < 2.5. This trend of river channel changes can be used as basis for evaluating river restoration works.